Comparative efficacy of carbendazim and prochloraz manganese against dry bubble, wet bubble and cobweb disease of button mushroom - Sharma, V P; Kumar, Satish (Mushroom Research, 2012)
Comparative effectiveness of carbendazim and Prochloraz manganese against the mycoparasites Lecanicillium fungicolaz, Mycogone perniciosa and Cladobotryum dendroides revealed that Carbendazim and Prochloraz manganese resulted in slight reduction in yield loss when applied immediately after casing and three days after casing to manage dry bubble disease. Carbendazim proved more effective in reducing the yield loss by wet bubble as compared to Prochloraz manganese irrespective of its application time. Application of Prochloraz manganese and carbendazim after three days of casing resulted in significant reduction in yield loss by cobweb.Â